2017
DOI: 10.20853/32-1-793
|View full text |Cite
|
Sign up to set email alerts
|

The effect of speaking English as a second language on the study of anatomy and physiology in the nursing programme

Abstract: The characteristics of students entering tertiary education, including nursing programmes has changed in recent years, with a large majority studying with English as a second language (ESL). There is a high attrition of students in first year nursing education, due to failure in Anatomy and Physiology (A&P). This study aimed to determine whether ESL affects nursing students' success in A&P and whether there was a relationship between matric scores and those of A&P. A quantitative descriptive survey design was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Additionally, many respondents (48%) reported that the language barrier contributed to failure of student nurses in A&P. Students are not taught in their vernacular, and all text books are written in the English language. According to Langtree et al, [11] ESL students have difficulties with the English language in the first semester of study, which affects the study of new and complex terms, which in turn negatively affects first-year nursing students and leads to high failure rates. [11] Students' home languages therefore have an influence on their performance at first-year level.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, many respondents (48%) reported that the language barrier contributed to failure of student nurses in A&P. Students are not taught in their vernacular, and all text books are written in the English language. According to Langtree et al, [11] ESL students have difficulties with the English language in the first semester of study, which affects the study of new and complex terms, which in turn negatively affects first-year nursing students and leads to high failure rates. [11] Students' home languages therefore have an influence on their performance at first-year level.…”
Section: Researchmentioning
confidence: 99%
“…According to Langtree et al, [11] ESL students have difficulties with the English language in the first semester of study, which affects the study of new and complex terms, which in turn negatively affects first-year nursing students and leads to high failure rates. [11] Students' home languages therefore have an influence on their performance at first-year level. An evaluation of a blended learning approach in an A&P module for nursing students revealed that participants encountered difficulties in using new and complex terms and concepts.…”
Section: Researchmentioning
confidence: 99%
“…Although the degree of difficulty and complexity of a module is subjective, many authors agree that nursing students generally perceive bioscience subjects to be difficult to learn and understand [ 3 , 5 , 17 , 18 ]. Two recent South African studies reflect students’ poor performance in bioscience [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%